PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, DAN KOMITE AUDIT TERHADAP INCOME SMOOTHING PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Mula Lumban Raja Simatupang; Herti Diana Hutapea; Danri Toni Siboro (Jurnal Akuntansi Kompetif, 2026)
This study aims to determine the effect of profitability, leverage, company size, and audit committee on income smoothing in banking companies listed on the Indonesia Stock Exchange for the 2022-2024 period. This study was conducted at banking companies. Data was accessed through the website www.idx.co.id.The sampling technique used purposive sampling, resulting in a population of 47 companies. A sample of 17 companies was obtained with an observation period of three (3) years. Therefore, the total number of data collected in banking companies was 51, meeting the research criteria. This is a quantitative study using secondary data sources obtained from annual financial reports on the Indonesia Stock Exchange (IDX). The analysis techniques used descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, t-tests, and coefficient of determination tests. Data processing was performed using SPSS 26 (Statistical Package for the Social Sciences) software.The results of the study indicate that profitability, leverage, and company size have no effect on income smoothing. Meanwhile, the audit committee significantly influences income smoothing. This means that the size of a bank's profits does not automatically drive management to engage in income smoothing. A company's debt level has also not been shown to be the primary reason for income smoothing. Companies of all sizes, both large and small, have similar tendencies toward income smoothing practices. The audit committee within a bank significantly impacts how the bank manages its profit stability.